PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS BUDAYA (PBB) TERHADAP HASIL BELAJAR IPS DAN KEAKTIFAN SISWA KELAS IV SD NEGERI 01 TRIDARMA WIRAJAYA - Firosalia Kristin (Universitas PGRI Yogyakarta, 2016)
This study aims 1) to determine differences in learning outcomes of students who take the social studies learning by using culture-based learning model with the conventional model, and 2) to determine the activity of students who take the learning culture based learning model with conventional models. This research is a quasi-experimental study. The study population was fourth grade students of SDN 01 Tridarma Wirajaya. Data were collected through a test to measure the results of social studies and observation to determine students' activity. Based on the analysis of data obtained: 1) There are differences in social studies learning outcomes between groups of students who take the learning culture based learning model with conventional learning. 2) There is a difference between the activity of groups of students who take the learning culture based learning model with conventional models.